Evaluation of utilization of digital library applications Universitas Muhammadiyah Sumatera Utara / Muhammad Arifin and Isva Affannura Khairi - Arifin, Muhammad; Khairi, Isva Affannura (2020)
The purpose of this study evaluates the use of UMSU Digital Library and the level of utilization of UMSU digital library applications. This study uses descriptive qualitative research. The study was conducted at the Library of the University of Muhammadiyah North Sumatra and the Campus Environment of the University of Muhammadiyah North Sumatra in January 2020. The informants of this study were the Head of the Library of the University of Muhammadiyah, North Sumatra, 10 users of UMSU academics and non-academics users of UMSU. Determination of informants using purposive sampling techniques Data collection is done by using in-depth interviews (depth interviews) and observation. The results showed that the lack of collections provided by the UMSU Digital Library application resulted in the low utilization of UMSU digital library applications by UMSU students and non-UMSU academic community users. And also UMSU Academic Non-civitas Users know the application from the Google and Google Play Store suggestions and references when they search and use online library keywords, curiosity makes them interested in using the UMSU digital library application.